Epoxy‐based gelcasting of machinable hydroxyapatite foams for medical applications. Issue 8 (13th March 2018) - Stastny, Premysl; Chlup, Zdenek; Kalasova, Dominika; Zikmund, Tomas; Kaiser, Jozef; Trunec, Martin
Abstract: Machinable hydroxyapatite foams for subtractive manufacturing of customized bone scaffolds have been developed. The foams were prepared by direct foaming of water‐based hydroxyapatite suspension with dissolved epoxy resin. The foams were consolidated by gelation of the epoxy‐based suspension in air atmosphere. The effect of processing conditions on the foam structure was investigated. The foams had a cellular‐like structure with interconnected pores. The sintered foam with 78% open porosity, the most frequent pore size 430 μm, and the most frequent interconnecting pore window size 150 μm, has been chosen as the foam with the optimal structure from the viewpoint of an application in bone regeneration. The compressive strength of this sintered foam reached 3.3 MPa. The machinability of the optimal foam was investigated using computer numerical controlled (CNC) milling of a test pattern. The milling tests were carried out with the foam at different processing stages and after impregnation with paraffin wax. The best milling result was obtained for a dried foam impregnated with paraffin. The applicability of the whole processing chain was demonstrated and a customized scaffold was manufactured.